Facile Synthesis and Applications of Flavonoid-heterocyclic Derivatives - Saba, Farooq; Zainab, Ngaini (Bentham Science, 2024)
Abstract: Flavonoids belong to the polyphenol group that naturally exists in fruits, vegetables, tea, and grains. Flavonoids, as secondary metabolites, show indispensable contributions to biolog-ical processes and the responses of plants to numerous environmental factors. The bioactivity of flavonoids depends on C6-C3-C6 ring substitution patterns that exhibit bioactive antioxidant, an-timicrobial, antifungal, antitumor, and anti-inflammatory properties. The synthesis of flavonoids has been reported by various methodologies. Therefore, the present review systematically sum-marizes the synthesis of recent heterocyclic flavonoid derivatives via facile synthetic approaches since the research in flavonoids is useful for therapeutic and biotechnology fields.